Phenomenology of Affectivity: form, color and image in Kandinsky’s abstract painting (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The present article analyzes the problem of affectivity in French philosopher Michel Henry's conception of Phenomenology of life, conceived of as the foundation of the subjectivity and the essence of the manifestation. Henry analyzes the work of the painter Vasily Kandinsky, showing how abstract and non-figurative painting expresses in colors and forms something invisible, which is the essence of the painting and coincides with the Life. Kandinsky's conception of abstraction refers to the invisible and the inner content, which expresses itself through colors and forms, being the life itself in its fundamental subjective pathos. In this way, the art becomes the only language capable to express the radicality of the affective life, because it does not represent anything exterior or foreign, being its content the life itself.
Keywords: Phenomenology; affectivity; abstract painting; Henry Kandinsky